Arthritis in idiopathic inflammatory myopathy: clinical features and autoantibody associations - Klein, Martin; Mann, Heřman; Pleštilová, Lenka; Betteridge, Zoe; McHugh, Neil; Remáková, Martina; Novota, Peter; Vencovský, Jiří (Journal of rheumatology, 2014)
OBJECTIVE: To determine the prevalence, distribution, and clinical manifestations of arthritis in a cohort of patients with idiopathic inflammatory myopathies (IIM). Associations with autoantibody status and HLA genetic background were also explored. METHODS: Consecutive patients with IIM treated in a single center were included in this cross-sectional study (n = 106). History of arthritis, 68-joint and 66-joint tender and swollen joint index, clinical features of IIM, and autoantibody profiles were obtained by clinical examination, personal interview, and review of patient records. High-resolution genotyping in HLA-DRB1 and HLA-DQB1 loci was performed in 71 and 73 patients, respectively. RESULTS: A combination of patients' medical history and cross-sectional physical examination revealed that arthritis at any time during the disease course had occurred in 56 patients (53%). It was present at the beginning of the disease in 39 patients (37%) including 23 cases (22%) with arthritis preceding the onset of muscle weakness. On physical examination, 29% of patients had at least 1 swollen joint. The most frequently affected areas were wrists, and metacarpophalangeal and proximal interphalangeal joints. Twenty-seven out of the 29 anti-Jo1-positive patients had arthritis at any time during the course of their illness; this prevalence was significantly higher compared to patients without the anti-Jo1 autoantibody (p < 0.0001). No association of arthritis with individual HLA alleles was found. CONCLUSION: Our data suggest that arthritis is a common feature of myositis. It is frequently present at the onset of disease and it may even precede muscular manifestations of IIM. The most common presentation is a symmetrical, nonerosive polyarthritis affecting particularly the wrists, shoulders, and small joints of the hands. We have confirmed a strong association of arthritis with the presence of the anti-Jo1 antibody.
Keywords: dospělí; Genotype; Female; Prevalence; Adult; ženské pohlaví; průřezové studie; komorbidita; lidé; Comorbidity; genotyp; HLA-DQ beta řetězec; myozitida; Humans; prevalence; Cross-Sectional Studies; Male; Arthritis; Aged; Autoantibodies; artritida; alely; Myositis; Alleles; HLA-DRB1 Chains; lidé středního věku; senioři; mužské pohlaví; HLA-DRB1 řetězec; Middle Aged; HLA-DQ beta-Chains; autoprotilátky